Sports activities in extended education—their leading role for educational development - Ferrari, Ilaria; Bretz, Kathrin; Kress, Johanna; Niederberger, Lukas; Schuler Braunschweig, Patricia (Frontiers in Education, 2025)
IntroductionPhysical inactivity represents a global challenge that calls for early intervention, particularly during childhood. Schools are uniquely positioned to influence children’s current and future physical activity behaviors. The introduction of all-day schools creates an opportunity to integrate diverse sports-oriented activities throughout the school day. In Zurich, the implementation of all-day schools in primary schools led to the development and evaluation of extended educational programes, with a particular emphasis on physical activities, with the aim of contributing to holistic and sustainable health promotion. These activities included optional programes during lunch breaks and before, between, and after lessons, aimed at fostering both subject-specific and interdisciplinary competencies.MethodsTo evaluate the activities, both qualitative and quantitative methods were used, comprising semi-structured interviews with school principals and extended educational services principals and student questionnaires.ResultsThe evaluation revealed high levels of participation, particularly in physical activities including the Open Gym and mobile facilities.DiscussionThe findings demonstrate the leading role of physical activities including teacher-led and child-driven options in extended educational programs.